1991
DOI: 10.1111/j.1365-2141.1991.tb08581.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood stem cell transplantation for chronic granulocytic leukaemia in transformation: a report of 47 cases

Abstract: Forty-seven patients with chromosome Philadelphia-positive (Ph1) chronic granulocytic leukaemia (CGL) in transformation underwent autologous transplantation of peripheral blood stem cells (ABSCT) collected at the original diagnosis before any treatment. They were treated with three consecutive strategies: single transplant (group I = 17 patients), double transplant (group II = 13 patients), double transplant followed by recombinant alpha interferon (group III = 17 patients). Forty-three patients were restored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…38 In addition, it has been shown that patients who do not respond cytogenetically to IFN␣, may revert to IFN␣ exactly evident from (n = 12)/ +G-CSF paper; 41% of (n = responsiveness after intensive chemotherapy and autoSCT. 39,40 All these studies suggest an additive effect of intensive chemotherapy to an already impressive antileukaemic activity of IFN␣ alone. A prospective randomised trial under the auspices of the EBMT addressing the question whether autoSCT followed by IFN␣ vs IFN␣ alone improves survival is currently being performed.…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, it has been shown that patients who do not respond cytogenetically to IFN␣, may revert to IFN␣ exactly evident from (n = 12)/ +G-CSF paper; 41% of (n = responsiveness after intensive chemotherapy and autoSCT. 39,40 All these studies suggest an additive effect of intensive chemotherapy to an already impressive antileukaemic activity of IFN␣ alone. A prospective randomised trial under the auspices of the EBMT addressing the question whether autoSCT followed by IFN␣ vs IFN␣ alone improves survival is currently being performed.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been proposed to purge autologous marrow in vitro to favor hematopoietic reconstitution with Ph-negative cells [ 151. These approaches include: 1) purging with chemotherapy [16][17][18] or interferon [19], 2) in vitro selection by growth in long-term culture [20], and 3) in vivo therapy with combinations of antileukemic agents or with interferon-alpha followed by transplant [21,22]. The use of peripheral blood progenitors has also been proposed [23,241.…”
Section: Discussionmentioning
confidence: 99%
“…5 The cells belonging to the before any treatment. 21 All patients were in chronic phase, malignant clone can be detected by either chromosome with 100% Ph-positive metaphases in cytogenetical analysis. analysis or techniques designed to monitor the expression of Informed consent was given in every case.…”
Section: Introductionmentioning
confidence: 99%